The risk factors and incidence of major infectious diseases in patients with ankylosing spondylitis receiving tumor necrosis factor inhibitors. Issue 6 (2nd November 2021) - Koo, Bon San; Lim, Yu-Cheol; Lee, Min-Young; Jeon, Ja-Young; Yoo, Hyun-Jeong; Oh, In-Sun; Shin, Ju-Young; Kim, Tae-Hwan
Abstract: Objectives: This study aimed to evaluate the risk factor and incidence of infections in patients receiving tumor necrosis factor inhibitor (TNFi) therapy for ankylosing spondylitis using data from the national health insurance service. Methods: This was a retrospective cohort study. Data regarding patients with ankylosing spondylitis prescribed TNFis were obtained from an insurance claims database of the Health Insurance Review & Assessment Service in Korea. Outcomes used were incidence rates of serious infection, pneumonia, tuberculosis, and herpes zoster during the follow-up period as well as the relationship between each TNFi and sex, hazard ratio (HR) of infection-related risk factors, and incidence of infections. Results: A total of 2515 patients were included. There were no significant differences among the hazard ratios of TNFis for serious infection, pneumonia, and herpes zoster. However, the hazard ratio of tuberculosis was significantly higher for infliximab than for etanercept (adjusted HR 8.40 [95% confidence interval: 1.06–66.91]). In the subgroup analysis by sex, women treated with golimumab had a significantly higher hazard of herpes zoster than those treated with etanercept (adjusted HR 12.40 [95% confidence interval: 1.40–109.58]). Conclusion: We recommend that risk factors for these infectious diseases be identified prior to prescribing TNFis in these patients.